2020
DOI: 10.1155/2020/6716103
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life among Patients with Hepatitis C Virus Infection: A Cross-Sectional Study in Jianping County of Liaoning Province, China

Abstract: Background. Patients with chronic liver disease (CLD) have extrahepatic manifestations and impaired health-related quality of life (HRQOL), and hepatitis C virus (HCV) infection is a leading cause of CLD, cirrhosis, and hepatocellular carcinoma (HCC). This study is aimed at assessing HRQOL in patients with HCV infection in the rural areas and identifying factors associated with impairment of HRQOL. Methods. A cross-sectional study was conducted in a county of Liaoning Province in northeast China. HRQOL of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
(31 reference statements)
3
6
0
1
Order By: Relevance
“…The patient population consisted of patients with autoimmune or cholestatic liver disease (19 studies), [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] chronic hepatitis B or C (35 studies), [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] NAFLD or NASH (15 studies), [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , …”
Section: Resultsunclassified
See 2 more Smart Citations
“…The patient population consisted of patients with autoimmune or cholestatic liver disease (19 studies), [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] chronic hepatitis B or C (35 studies), [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] NAFLD or NASH (15 studies), [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , …”
Section: Resultsunclassified
“… 9 , 12 , [22] , [23] , [24] , [25] , [26] Mental, physical, and social factors, such as body composition, comorbidities, fatigue, lack of information on the disease, and low income together with patient characteristics, such as younger age at diagnosis, alcohol use, and female sex, were associated with impaired quality of life. 8 , 10 , 11 , 15 , 18 , 21 , 30 , 33 , 35 , [42] , [43] , [44] , 48 , 49 , 58 , 59 , 66 , 67 , 72 , 74 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 7 ) The EuroQol Group 5 Dimension (EQ‐5D) is designated as one of the most preferred tools for quantifying HRQoL in the general population and in a pathological entity, namely, chronic liver disease where its validity has been widely affirmed. ( 8 , 9 , 10 , 11 , 12 , 13 ) The EQ‐5D questionnaire covers a broad array of health issues, including mobility, self‐care, usual activities, pain and anxiety/depression, and subsequently generating a utility index. Of note, it is advantageous to compare the retrieved utility index among different studies in case of lacking control groups or available population norms.…”
mentioning
confidence: 99%
“…Previous studies had shown that assessing HRQOL is of utmost importance to community health. It was reflected to be the gold standard to report pay papatients'xperiences with both illness and treatment (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%